Аналіз методів компресії зображень формату JPEG для підвищення рівня стиснення - Курлан, О. О.; Омельченко, С. В. (ХНУРЕ, 2021)
The fundamental theoretical techniques of image compression are considered. Their comparative analysis was performed. Approaches of images compression level increasing presented in JPEG format will be investigated. In the practical part, there will be a software implementation of the investigated approaches and a comparative characteristic.
Keywords: JPEG; PSNR; image compression level; RD-OPT